2021 IEEE International Conferences on Internet of Things (iThings) and IEEE Green Computing &Amp; Communications (GreenCom) An 2021
DOI: 10.1109/ithings-greencom-cpscom-smartdata-cybermatics53846.2021.00020
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Regression Approach for Throughput Estimation in an IoT Environment

Abstract: The success of Internet of Things (IoT) has significantly increased the volume of data generated by various smart applications. However, as many of these applications are characterized by strict Quality of Service (QoS) requirements, there is a growing need for accurately predicting typical performance parameters such as throughput. This prediction should be based on the applications' traffic profiles and at the same time reflect the network uncertainty that IoT access networks add to the overall communication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Authors in [131] included prior knowledge in information fusion to train neural networks and achieved a 10% improvement over statistical traffic predictions. Similarly, authors in [132] and [133] were able to achieve MAE of 0.3 and 0.002% using LSTMs and regression models respectively. Authors in [140] were able to achieve a Root Mean Square Error (RMSE) of 0.0298 in their prediction accuracy with 500 units in their LSTM model.…”
Section: Role Of Ai and ML In Distributed Network Management And Edge...mentioning
confidence: 87%
See 2 more Smart Citations
“…Authors in [131] included prior knowledge in information fusion to train neural networks and achieved a 10% improvement over statistical traffic predictions. Similarly, authors in [132] and [133] were able to achieve MAE of 0.3 and 0.002% using LSTMs and regression models respectively. Authors in [140] were able to achieve a Root Mean Square Error (RMSE) of 0.0298 in their prediction accuracy with 500 units in their LSTM model.…”
Section: Role Of Ai and ML In Distributed Network Management And Edge...mentioning
confidence: 87%
“…AI & ML techniques such as Long Short Term Memory (LSTM) [132] and regression models (Decision Tree Regression, Gradient Boosted Regression Tree, K-Nearest Neighbour Regression, Support Vector Regression etc.) [133] are promising tools to understand time dependencies and accurately forecast/estimate user requirements. LSTMs were able to achieve the MSE and MAE of 0.05 and 0.3 respectively while regression models achieved MSE and MAE of 0.004 and 0.002 respectively for different traffic predictions tasks indicating their potential to perform this task accurately [132], [133].…”
Section: Traffic Prediction At the Edgementioning
confidence: 99%
See 1 more Smart Citation
“…There are also few recent studies that applied regression based approaches [12], [13], to predict throughput and packet delivery ratio (PDR), since regression based techniques tend to be a light weight alternative for the prediction of QoS metrics. However, most of the IoT data used for the QoS prediction consist of time series sequences which are better predicted using deep learning approaches, such as Recurrent Neural Networks (RNN) or Long Short-Term Memory (LSTM) networks, that are specifically designed for handling time series data.…”
Section: A Deep Learning For Qos Predictionmentioning
confidence: 99%
“…Nonetheless, various research gaps can be identified in these existing studies. Firstly, in [8]- [13] several QoS prediction mechanisms are presented, however, without considering any time dependencies. Secondly, for the works [14]- [17], only a simple traffic prediction is provided, without predicting typical QoS metrics found in an IoT context.…”
Section: Introductionmentioning
confidence: 99%